2009
DOI: 10.4067/s0717-95022009000100001
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics and Haematological Studies in Wistar Rats Subjected to Prolonged Treatment of Chloramphenicol

Abstract: OYEYEMI, M. O. & ADENIJI, D. A. Morphological characteristics and haematological studies in Wistar rats subjected to prolonged treatment of chloramphenicol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The adverse effects of these drugs on sperm characteristics were apparently evident in combined therapy group. Oyeyemi and Adeniji [19] have reported that administration of CAP alone for 20 and 25 days decreased sperm concentration and motility as well as elevated sperm abnormality. One of the important developments in the last two decades in the study of human being infertility has been the discovery of ROS and the role of associated oxidative stress in the aetiology of defective sperm function and male infertility [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse effects of these drugs on sperm characteristics were apparently evident in combined therapy group. Oyeyemi and Adeniji [19] have reported that administration of CAP alone for 20 and 25 days decreased sperm concentration and motility as well as elevated sperm abnormality. One of the important developments in the last two decades in the study of human being infertility has been the discovery of ROS and the role of associated oxidative stress in the aetiology of defective sperm function and male infertility [40].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such drugs include cisplatin [15], sulfasalazine [16], doxorubicin [17] and tetracycline [18]. Changes in morphological characteristics of sperm of rats exposed to CAP have been reported [19]. In this study, we investigated the sequential changes in the levels of oxidative stress‐related parameters to understand the testicular response after exposure to therapeutic doses of CAP and multivitamins and haematinics complex.…”
mentioning
confidence: 99%
“…There have been increasing numbers of reports about the ecotoxicological effects of these two kinds of antibiotics. [36][37][38] Obviously, any chemical that affects the function of a target biomolecule causes toxicity only when it penetrates the cell, must first cross the cell membrane. 39 The toxicity-causing mechanisms of exogenous chemicals have been elucidated but they often focus on the interactions with target molecules, [40][41][42][43][44][45] errors in protein expression, 46 alteration of gene sequences 38 and dose-effect relationships.…”
Section: Introductionmentioning
confidence: 99%